Nomadic Societies in the Middle East and North Africa : Entering the 21st Century - Chatty, Dawn, (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2006)
A scholarly volume devoted to an understanding of contemporary nomadic and pastoral societies in the Middle East and North Africa. This volume recognizes the variable mobile quality of the ways of life of these societies which persist in accommodating the 'nation-state' of the 20th and 21st century but remain firmly transnational and highly adaptive. Composed of four sections around the theme of contestation it includes examinations of contested authority and power, space and social transformation, development and economic transformation, and cultures and engendered spaces.